Cross-Cultural Ties between Ghana and Egypt: The Agency of the Egyptian Community in Accra, Ghana - Agyeman, Edmond Akwasi; Amoako-Gyampah, Akwasi Kwarteng (African Human Mobility Review, 2021)
Ghana is recognized as an important destination of international migrants. Inspite of the socio-economic and political upheavals that the country experiencedduring the early post-independence era leading to the (forced) return of severalof its migrant groups, some have still remained and formed permanentcommunities and integrated into the Ghanaian society. This paper focuses on theEgyptian diaspora in Ghana. It examines: (1) the type of cross-border andtransnational ties that Egyptian migrants in Ghana have established betweenGhana and Egypt; (2) how these ties generate cross-cultural relations betweenGhana and Egypt; and (3) the extent to which these ties provide a privilegedeconomic and political position to the Egyptian community in Ghana. The workis based on the socio-cultural transnationalism theory. A socio-historical methodwas adopted for the research and apart from the analysis of historical data, eightkey informants were interviewed. The paper shows that due to high-profileintermarriages between Ghanaians and Egyptians, coupled with the ‘Nkrumahfactor’, the Egyptian community in Ghana occupies a privileged economic andpolitical position in Ghana.